U-Pb ages of detrital zircon and provenances of Red Clay in the Chinese Loess Plateau. (1st May 2017) - Gong, Hujun; Xie, Wenbin; Zhang, Rui; Zhang, Yunxiang
Graphical abstract: Highlights: More than 1000 U-Pb ages of detrital zircon from the Red Clay sequences in the Chinese Loess Plateau are presented. Provenances of Red Clay vary with time and are generally comparable with those of North Pacific dusts. There is a good correlation between provenances of the dust deposits and terrestrial environmental change. Abstract: The Chinese Loess Plateau (CLP), which is located in the central part of China, mainly contains two sequences: the Quaternary loess-paleosol sequence and the late Miocene-Pliocene Red Clay sequence. U-Pb ages of detrital zircon from the Quaternary loess-paleosol sequences indicate that the current spatial pattern of central Asian aridification was largely established during the early Quaternary. U-Pb ages of detrital zircon from the underlying Red Clay sequences demonstrate that the northern source regions were important contributors for the dust since the late Miocene, except for the periods of ∼8 Ma and ∼5.5 to ∼4 Ma. These two periods correspond to increased and decreased dust deposition in the North Pacific, respectively, ascribed to the late Miocene aridification of the Qaidam Basin (in the west of the CLP) and the early Pliocene aridification of the Tarim Basin (in the west of the CLP). We attribute the increase of the Qaidam Basin-derived North Pacific dust fluxes to the uplift of the NE Tibetan Plateau. Such uplift also controlled the climatic and environmental changes in central Asian during the late Miocene. This study highlights the dynamical process of the central Asian aridification during the late Miocene-Pliocene.